Building Information Modeling in the Architecture-engineering Construction Project in Surabaya. (2017) - Chandra, Herry Pintardi; Nugraha, Paulus; Putra, Evan Sutanto
Abstract: In current practice, many digital models do not contain sufficient information from designers to contractors and operators. A great deal of literature has pointed to the importance of understanding the Building Information Modeling (BIM). BIM is a digital representation of the physical and functional characteristics of a building. In Architecture-Engineering-Construction, BIM is the development and use a computer software model to stimulate the construction and operation of a facility, to make decisions and to improve the process of delivering the facility. The aims of this paper are to explore the need of technological support to implement the site-linked of BIM, the benefits of BIM, and the challenges of BIM. The research was conducted through literature review of BIM. The data was collected from the questionnaire survey carried out to 26 valid responses within the main stakeholders of construction work in Surabaya. A questionnaire is prepared by incorporating the technological support, benefits, and challenges of BIM. The data was analyzed by using descriptive analysis including mean analysis with 5 Likert scale. The results of the research shows that the need of technological support to implement the BIM is parametric components (mean value of 4.46), the need of software package majority is prepared by contractor and construction management consultant, and the benefit of BIM is to reduce the construction cost (mean value of 4.6). In addition, the main challenge of BIM is different brand with the mean value of 4.27, in which of incompatibility of different brand (mean value of 4.31.